Mademoiselle Mom - Parent, Nancy; Disney Storybook Artists; Disney Enterprsies (1996- ) (New York, NY : Harper, an imprint of HarperCollinsPublishers, 2019)
When her mom gets sick, Nancy decides to help around the house by cleaning up and watching her sister JoJo.
"Based on the episode by Sarah Katin and Nakia Trower Shuman."
"Disney junior"--Cover.
Ages 4-8.
Guided reading level J.
107905
Keywords: Fancy Nancy -- (Fictitious character) -- Juvenile fiction; Helping behavior -- Juvenile fiction; Readers -- Beginner; Media Tie-In.; Imagination & Play; Juvenile fiction / Readers / Beginner